Possible implications of the price, cross-price and income elasticities of public bus transport in the Cape Metropolitan Area : a co-integration approach - Neubrech, Stefan Eduard (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Econ.) -- University of Stellenbosch, 1997.